Contemporary Banking Theory - Bhattacharya, Sudipto; Thakor, Anjan V. (Journal of Financial Intermediation, 1993)
We review the contemporary theory of financial intermediation. The focus is on contributions in the past 15 years or so that have advanced our understanding of why financial intermediaries exist, the credit allocation and other services they provide in spot and forward credit markets, the contractual nature and allocational consequences of the claims they issue, and the optimal design of bank regulation. Journal of Economic Literature Classification Numbers: 310, 312, and 314.